Economic globalization and institutions of global governance - Griffin, Keith (2003)
Economic globalization is reducing the significance of stateboundaries. We have a global economy but lack the institutions necessary for a global polity. Unilateral action by a would-be hegemon is untenable in the long term and hence there is a need to discuss our institutions of global governance. The benefits and costs of globalization, have been distributed asymmetrically, placing poor people in poor countries at a disadvantage, especially as regards the free movement of low-skilled labour and creation of intellectual property rights. The World Trade Organization, a target of the critics of globalization, should be seen as a welcome extension of the rule of law to the international arena and a counterweight to unilateralism. More generally, global economic liberalism should be balanced by institutions which provide global public goods and international mechanisms to finance them. All of this implies a further weakening of state sovereignty and a need to ensure that global institutions are democratic and can be held accountable to people worldwide for their performance. - Reproduced.
Keywords: Globalization